Praxeological analysis of number patterns through the anthropological theory of the didactic perspective - Pradipta, Trisna Roy; Turmudi, Turmudi; Hendriyanto, Agus; Pramartha, I Nyoman Bagus (Universitas Islam Negeri Raden Intan Lampung, 2025)
Number pattern material is important to study because it serves as a bridge between arithmetic and algebra, playing a strategic role in developing junior high school students' algebraic thinking, mathematical reasoning, and mathematical literacy. This study employs Yves Chevallard's Anthropological Theory of the Didactic (ATD) to analyze the praxeological, epistemic, systemic, and heuristic aspects of mathematical knowledge in Grade VIII number pattern textbooks. The methodology employed is document analysis using a praxeological framework comprising four components: types of tasks, techniques, technology, and theory. The study reveals that the textbook presents a strong mathematical organization in the praxis-praxeological aspect (tasks and techniques), with various examples of number patterns, including triangular numbers, square numbers, the Fibonacci sequence, and arithmetic and geometric sequences. However, the logos aspect (technology and theory) remains implicit and limited. The epistemic aspect shows knowledge presented through an inductive approach from concrete pattern observation to generalization. The systemic aspect demonstrates coherent structure with three interrelated main learning activities. The heuristic aspect shows dominance of pattern-finding strategies through tables and geometric visualization. The implications of this research emphasize the importance of developing the logos aspect in mathematics textbooks to strengthen students’ conceptual understanding and encourage metacognitive reflection.